2010
DOI: 10.1086/653111
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Supplementation in HIV‐Infected Individuals in South India: A Prospective Interventional Study

Abstract: Macronutrient supplementation did not result in significantly increased weight gain compared with standard care (including nutritional counseling) among patients with moderately advanced HIV disease. The effect of supplementation on specific subsets of patients and on preserving immune function needs further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 22 publications
5
37
0
1
Order By: Relevance
“…Poor absorption of nutrients that may be the result recurrent/chronic diarrhea and HIV-caused intestinal cell damage. And then the will develop malnutrition again it contributes to immune impairment, making the body vulnerable to frequent illnesses [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Poor absorption of nutrients that may be the result recurrent/chronic diarrhea and HIV-caused intestinal cell damage. And then the will develop malnutrition again it contributes to immune impairment, making the body vulnerable to frequent illnesses [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In another observational study in Zambia, a monthly WFP individual or household food ration was not associated with weight gain or BMI increases (after adjusting for a small set of baseline characteristics) at 6 and 12 months among PLHIV on ART, compared to the control group [41]. A third observational cohort study in India found a small daily WFP individual supplement provided to adult PLHIV on ART was not associated with improvements in weight, BMI, MUAC or hemoglobin concentrations at 6 months, compared to those in two comparison clinics after adjusting for baseline CD4 count, age, and sex [43]. Lastly, in a retrospective observational cohort study from Uganda using a large program administrative database, individuals receiving food assistance for a period of 12 months had a higher mean weight gain compared to their matched control, and had statistically significant, but biologically insignificant slower disease progression ( [30]).…”
Section: Discussionmentioning
confidence: 97%
“…First, it is one of only a handful of studies investigating the impact of food assistance to adult PLHIV in a developing country context [30,[41][42][43];…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have shown that adequate nutrition and modified lifestyle associated with or without education and counseling can improve nutritional status both during stable treatment free period and during severe episodes of the infection [2,12,27,28]. In this study, the authors also investigated the effects of nutritional education and lifestyle modification on the nutritional status of treatment naïve HIV patients in Yaoundé, Cameroon.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed the beneficial effects of these factors in improving nutritional status, though mostly short termed and based on the use of nutritional supplements, which are expensive for HIV patients in resource limitted settings [12][13][14].…”
Section: Introductionmentioning
confidence: 99%